Two in one: explaining the management of the Okavango Delta World Heritage Site, Botswana - Matswiri, Gertrude Mamotse (Department of Archaeology, 2018)
Because of their outstanding universal significance, World Heritage sites are worthy of special protection by the international and local communities. They obtain this status after being listed under the UNESCO 1972 Convention Concerning the Protection of the World Cultural and Natural Heritage. In previously colonised regions such as Africa, the conservation and management of World Heritage is based on international laws and modern management systems introduced after conquest. However, the process protects mostly the universal values on which the inscription of the site was based. This often marginalises local values and local management systems which are important to local communities. It also alienates local communities from their heritage which they have protected for many years. This research explores the relationship between modern and traditional management systems in the Okavango Delta Natural World Heritage site. It will focus on understanding the local values of the site, the current management system and traditional practices of the local communities. The expected outcome is to develop a syncretic management system influenced by the traditional and the modern. It is hoped that such a system will not privilege one type of value over others.